A Study of Teaching Techniques Used By The Teachers of Speech Impaired Students and The Influences Towards Learning Achievements in Tenth and Eleventh Grade at SLB Dharma Bhakti Dharma Pertiwi in Academic Year 2017/2018 - Aprillia, Ayu; Sidabalok, Dameria Magdalena (Journal of English Education Studies, 2019)
The objectives of this research are to know the techniques used by the teacher in SLB Dharma Bhakti Dharma Pertiwi to teach English for speech impaired students, and to know how the techniques influence the students learning achievement. The research was done at SLB Dharma Bhakti Dharma Pertiwi in tenth and eleventh grade class in speech impaired class that consisted of 7 and 6 students. Data gathering was done by doing observation and interview to two teachers from ten and eleventh class. The results show that both teachers used mixed techniques in teaching English for speech impaired students. The teacher used some techniques like demonstration, repetition, and discussion. Demonstration can be done by showing pictures, using tools and touching the under part of the chin to teach pronunciation. Repetition can be done by repeating the words for many times to make the students remember. Discussion can be done by asking them questions to make the students active in the class. Some techniques were appropriate to improve students learning achievement but, there was a technique also that did not have a big impact in improving students learning achievement. By doing this research, it will help us to determine techniques in teaching speech impaired students. We know which technique that can help us to improve students learning achievement. It will help the students to get a better teaching learning process if we already know how to teach them.